1995
DOI: 10.1021/jm00008a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vivo Evaluation of Prodrugs of 9-[2-(Phosphonomethoxy)ethoxy]adenine

Abstract: A number of esters and amides of the anti-HIV nucleotide analogue 9-[2-(phosphonomethoxy)-ethoxy]adenine (1) have been synthesized as potential prodrugs and evaluated for oral bioavailability in mice. Dialkyl esters 17-20 were prepared via a Mitsunobu coupling of alcohols 8-11 with 9-hydroxypurine 12 whereas (acyloxy)alkyl esters 25-33 and bis-[(alkoxycarbonyl)methyl] and bis(amidomethyl) esters 34-39 were obtained by reaction of 1 with a suitable alkylating agent. Phosphonodichloridate chemistry was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Thus, Serafinowska et al reported the synthesis of acyclophosphonate prodrug 538 (259) in 15% yield by treatment of ethyl phosphonate derivative 535 with TMSBr, reaction of the corresponding silyl ester 536 with PCl 5 , and reaction with alanine methyl ester hydrochloride in the presence of triethylamine and NMI (Scheme 167). …”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…Thus, Serafinowska et al reported the synthesis of acyclophosphonate prodrug 538 (259) in 15% yield by treatment of ethyl phosphonate derivative 535 with TMSBr, reaction of the corresponding silyl ester 536 with PCl 5 , and reaction with alanine methyl ester hydrochloride in the presence of triethylamine and NMI (Scheme 167). …”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…Treatment of the aldehyde 2 with O-benzylhydroxylamine gave the oxime, which was then reduced without prior isolation with sodium cyanoborohydride and hydrochloric acid to yield the O-(benzylhydroxylamino)propylphosphonic acid diethyl ester 3 [6]. Acetylation to 4 and subsequent reaction of 4 with trimethylbromosilane [7] and hydrolysis of the re- sulting silylester with water yielded the O-benzyl protected FR900098 5.Phosphonic acid 5 was then coupled with commercially available chloroacetic acid methylester or chloromethyl pivalate, respectively, in DMF in the presence of triethylamine leading to the phosphonic acid diesters 6a and 6b [8]. This method was unsuccessful in the case of 1-chloroethyl pivalate and 1-chloroethyl benzoate.…”
mentioning
confidence: 99%
“…This method was unsuccessful in the case of 1-chloroethyl pivalate and 1-chloroethyl benzoate. However, when the phosphonic acid 5 and the chloroalkyl esters [9] were reacted in N, NЈ-dimethyl-N,NЈ-propyleneurea (DMPU) in the presence of triethylamine and sodium iodide, the bis(acyloxy)alkyl esters 6cϪg and 6k were obtained as diastereomeric mixtures [8]. Removal of the protecting groups with hydrogen and 10 % Pd/C in methanol gave the prodrugs 7aϪg and 7k.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been described that short alkyl chain esters of phosphonates are metabolically quite stable. 56,57 Incubation with rat liver microsomes showed that both compounds, 19a and 19c, were relatively stable toward liver enzymes. Only a very small percentage (<5%) was metabolized under the applied conditions (see Experimental Section), while >95% of the compounds were recovered unchanged.…”
Section: Investigation Of Chemical and Metabolic Stabilitymentioning
confidence: 99%